2010
DOI: 10.1186/1423-0127-17-56
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and laminin promote differentiation of human mesenchymal stem cells into insulin producing cells through activating Akt and ERK

Abstract: BackgroundIslet transplantation provides a promising cure for Type 1 diabetes; however it is limited by a shortage of pancreas donors. Bone marrow-derived multipotent mesenchymal stem cells (MSCs) offer renewable cells for generating insulin-producing cells (IPCs).MethodsWe used a four-stage differentiation protocol, containing neuronal differentiation and IPC-conversion stages, and combined with pellet suspension culture to induce IPC differentiation.ResultsHere, we report adding extracellular matrix proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Many types of differentiation protocols have been developed, which ultimately led to achieve the desired results confirming the presented theory (Gao et al 2008;Lin et al 2010;Oh et al 2004). …”
Section: Differentiation Of Other Types Of Mscsmentioning
confidence: 54%
See 1 more Smart Citation
“…Many types of differentiation protocols have been developed, which ultimately led to achieve the desired results confirming the presented theory (Gao et al 2008;Lin et al 2010;Oh et al 2004). …”
Section: Differentiation Of Other Types Of Mscsmentioning
confidence: 54%
“…These proteins enhanced pancreatic differentiation from MSCs: stimulated insulin and GLUT2 gene expressions, increased proinsulin and insulin protein levels. Moreover they enhanced insulin secretion in response to glucose stimulation and accumulation of insulin granules in IPCs (Table 3) (Lin et al 2010). Gao et al (2008) have indicated that extracellular matrix gel plays an important role not only in differentiation of human umbilical cord blood derived MSCs into IPCs, but also in maturation and formation of three dimensional structures.…”
Section: Differentiation Of Other Types Of Mscsmentioning
confidence: 99%
“…Other in vitro murine studies have shown that BM mesenchymal stem cells (MSCs) can be directly differentiated into insulin producing cells capable of reversing hyperglycemia after transplantation in diabetic animals (49,50). In vitro generation of insulin producing cells from human BM and umbilical cord MSCs have also been reported (51,52). However, the functionality and glucose responsiveness of these cells are unclear.…”
Section: Patient-specific Cell Sourcesmentioning
confidence: 99%
“…23 More recently, targeted activation of crucial pancreatic transcription factors successfully generated insulin-secreting cells; 24,25,26,27 however, because these methods depend largely on the use of lentiviral vectors, their potential for clinical use is restrained. 28,29,30,31 …”
Section: Introductionmentioning
confidence: 99%